EFEKTIVITAS MEDIA PAPAN MENEMUKAN TERHADAP KEMAMPUAN MENGENAL HURUF ANAK USIA DINI KELOMPOK B2 DI RA UMDI TAQWA PAREPARE - Nur'afia Hamka Hamka; Syarifah Halifah; Tien Asmara Palintan (IAIN Parepare, 2023)
Children's ability to recognize letters still uses the method of bolding letters. The aim of this research is to introduce finding board media to improve the ability to recognize letters in early childhood. This research uses descriptive qualitative research methods. Data collection techniques in this research include observation, interviews and documentation. The subjects used in this research were group B2 RA UMDI TAQWA Parepare, totaling 12 children, 5 boys and 7 girls. Children's ability to recognize letters has increased by using finding board media.